Narrow Band Imaging versus White Light for the Detection of Sessile Serrated Colorectal Lesions - Ferreira, Alexandre Oliveira (2023)
Funding Information: The authors would like to acknowledge the support of the Portuguese Society of Gastroenterology by granting the use of the REDCap software. Study data were collected and managed using REDCap (Research Electronic Data Capture) tools hosted at Sociedade Portuguesa de Gastrenterologia. REDCap is a secure, Web-based software platform designed to support data capture for research studies, providing (1) an intuitive interface for validated data capture; (2) audit trails for tracking data manipulation and export procedures; (3) automated export procedures for seamless data downloads to common statistical packages; and (4) procedures for data integration and interoperability with external sources. Publisher Copyright: © 2022 The Author(s). Published by S. Karger AG, Basel.